37th Annual Hawaii International Conference on System Sciences, 2004. Proceedings of The 2004
DOI: 10.1109/hicss.2004.1265486
|View full text |Cite
|
Sign up to set email alerts
|

Customers as part of value Webs: towards a framework for webbed customer innovation tools

Abstract: As the classical corporate boundaries are beginning to blur internally as well as externally traditional value chains loose their chain attributes, and are replaced by a web of fluid and flexible relations -the value web. This paper will extend the common view of value webs by defining customers as an important part of value creation. Customer integration into innovation processes taking place within a value web (a process that will be coined "webbed customer innovation" in this paper) is discussed as a benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…In order to effectively identify different types of customers, the market researchers of C P 0 collect information about the product application knowledge, product object knowledge and product innovation passion of customers by questionnaire (Reichwald et al 2004;Yang et al 2008a, b), on which the data analyst divides these K customers into ordinary customers group, creative customers group and leading customers group. Let OG = {1, 2, 3, .…”
Section: Hybrid Cprs Of Crs Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to effectively identify different types of customers, the market researchers of C P 0 collect information about the product application knowledge, product object knowledge and product innovation passion of customers by questionnaire (Reichwald et al 2004;Yang et al 2008a, b), on which the data analyst divides these K customers into ordinary customers group, creative customers group and leading customers group. Let OG = {1, 2, 3, .…”
Section: Hybrid Cprs Of Crs Methodsmentioning
confidence: 99%
“…Urban and Von Hippel (1988) and Lüthje and Herstatt (2004) suggested that an evaluation indicators system of lead users can be established from two aspects of "lead the trends" and "benefit expectations", and also pointed out that the questionnaire and cluster analysis method can be used to identify a lead user group. Reichwald et al (2004) used the object knowledge and application knowledge which customers master to identify four different types of customers: freshman, nerd, intuitive and pro. Berthon et al (2007) discussed the similarities and differences between "lead users" and "creative consumers".…”
Section: Customer Collaborative Production Innovation (Ccpi)mentioning
confidence: 99%
“…The Survey is the most disseminated method used in practice as well as in research to gather customers' opinion, respectively customer knowledge (Reichwald et al 2004). Here, interviews can be carried out personally, telephonically or by mail (Hemetsberger and Füller 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they have instead equipped customers with tools to design and develop their own products (toolkits), ranging from minor modifications to major innovations (Thomke and von Hippel, 2002). Besides toolkits, there are various tools to foster user based innovation like web based surveys, lead-user-method, virtual communities, group discussions, idea competition, brainstorming, workshops, customer idealized design, concept test, open source and focus groups, simulation, modeling, virtual reality, data mining and rapid prototyping technologies and many more alternatives (Reichwald, et al, 2004;Dodgson, et.al., 2006). Clearly it could be stated that the emergence of internet to the daily lives of people have made it a lot easier for companies to integrate users to the innovation process via web based tools.…”
Section: Discussionmentioning
confidence: 99%